Analisis Kesulitan Guru dalam Menggunakan Media Digital untuk Pembelajaran Sun, Moon, and Earth di SD - Anastasia Desmeria Br Ginting; Eva Betty Simajuntak; Josephine Dwi Inarly Situmorang; Margaretha Tresia Sirait; Ria Bernadetta Sitepu; Tiorina Sigalingging (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to analyze the difficulties faced by teachers in utilizing digital media for teaching the Sun, Moon, and Earth concepts in English at primary schools. The research employs a qualitative approach through case studies conducted at SDN 060842 Sekip Medan. Findings reveal that limited facilities, lack of teacher proficiency in technology, and distractions during lessons are significant challenges. Despite these hurdles, the use of digital media is crucial for enhancing students' understanding of abstract concepts, as it provides interactive learning opportunities. The study proposes several solutions, including training sessions for teachers and increasing access to technological resources, to improve the integration of digital media into classroom instruction.